PENGARUH PENERAPAN PEMBELAJARAN AKTIF TIPE COLLEGE BALL TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 14 PADANG - Yulia, Elfina; Aima, Zulfitri; Rahima, Rahima (STKIP PGRI Sumbar, 2013)
In this era, there were so many students did not understand about mathematical well, it can prove by many students who gets low score. The purpose of this research to know the improvement of the lesson activity of students in VIII SMPN 14 Padang. And also to know the students understanding about mathematical concept by applying active types College Ball teaching strategy better than using conventional teaching stategy for students understanding. The type of this research was the VIII class of SMPN 14 Padang years 2013/2014. The sample of this research is taken by random. The experiment class was VIII2 and the control class was VIII3. The instrument of this research was the observation sheets in students learning activity and also the test for mathemarical understanding concept. The type of test was essay test. The techniques of data analysis was using test for one group by MINITAP software. The result of this research indicated that the students activity consist of oral and writing activities in mathematical learning by using active type College Ball teaching strategy has improvement. The hypothesis test by using MINITAB software in test, is got P-value smaller than Î± was accepted. So we can conclude that the students understanding in mathematical concept in the VIII class of SMPN 14 Padang which is use active type College Ball teaching strategy was better than the mathematical concept in the control class with conventional teaching strategy.